An Engineer's View of the Problem of Economic Stability and Economic Regulation - Tustin, A. (Review of Economic Studies, 1951)
Journal Article An Engineer's View of the Problem of Economic Stability and Economic Regulation Get access A. Tustin A. Tustin Birmingham Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 2, 1951, Pages 85–89, https://doi.org/10.2307/2295736 Published: 01 July 1951